DECARBONIZING ELECTRICAL SUBSTATIONS: AN INTEGRATIVE REVIEW OF GREEN TECHNOLOGIES AND SUSTAINABLE PRACTICES ACROSS THE INFRASTRUCTURE LIFE CYCLE - Ali, Sulthan Syah; Berawi, Mohammed Ali; Sari, Mustika (Smart City, 2026)
Decarbonization of electrical infrastructure s becoming increasingly important in efforts to meet climate change mitigation targets, particularly in reducing emissions from substations. However, conventional substations continue to release significant quantities of GHG emissions throughout their life cycle As an example, a typical 500 kV substation emits around 150,000 tCO2e from construction to decommissioning. In addition, the development of green substation concepts remains limited, particularly in Indonesia where standardized approaches are not yet established. In response to the need for more sustainable power infrastructure, this study aims to identify, classify, and review all types of green technologies, practices, and innovations that can enhance conventional substation design, with the aim of reducing life cycle greenhouse gas emissions. An integrative literature review was conducted by synthesizing recent peer-reviewed studies related to green technologies and sustainable infrastructure. The identified technologies are categorized into seven groups, including Green materials, Efficient Construction Methods, Water Management, Thermal Management, Renewable Energy, Smart Monitoring System, and Low-Emission Equipment. The findings indicate that several technologies, such as Geopolymer Concrete as a replacement of Ordinary Portland Cement (OPC) Concrete, prefabricated construction to replace concrete columns and beams, implementation of passive design strategies for the substation building, and photovoltaic (PV) integration on substation roof to partially replace the grid electricity consumption have significant potential to reduce the GHG emissions across the substation life cycle. Overall, this study provides a comprehensive overview of green technologies, practices, and innovations that can be proposed as practical recommendations for the implementation in substation, contributing to the development of sustainable power infrastructure.